EFFECTS OF USING ENGLISH PODCASTS ON IDIOMS AND VOCABULARY LEARNING OF IRANIAN EFL LEARNERS - Tabatabaee, Golyas Akhavan; Rezvani, Ehsan (Universitas Kuningan, 2019)
This study is an attempt to explore the potential effects of using podcasts on idiom and vocabulary learning of Iranian EFL upper and lower intermediate learners as well as their attitudes toward learning via podcasts. To achieve the goals of the study, 100 participants who are made homogeneous in terms of language proficiency using an Oxford Placement Test (OPT) are selected, and are subsequently divided into four groups: two experimental groups and two control groups. Those students whose scores fall two standard deviations above the mean are considered as the upper intermediate group and those whose scores fall two standard deviations below the mean constituted the lower intermediate group. Then, researcher make vocabulary and idiom pre-tests are administered to assess the learners’ knowledge of the target vocabulary and idioms prior to treatment. As for the treatment, the students in the control group are taught conventionally using the readings in an ELT textbook, whereas the experimental groups’ learners are taught using podcasts containing idioms and vocabulary in focus. Finally, the learners are given a post-test parallel in form to the pre-test. The findings indicate that the learners who are taught via podcasts outperformed the control group on the post-test. Moreover, the findings show that learners have a significantly positive attitude toward learning via podcasts. The results will have implications for EFL teachers and materials developers.